Indonesian Cultural Empathy Scale (ICES): Development and Validation of a Contextualized Measure - Lailatul Badriyah; M. Furqon; Miftahul Jannah; Kurnia Rahmad Dhani (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Multicultural societies require culturally grounded instruments to assess empathy in ways that reflect local religious, communal, and national value systems. However, widely used empathy scales are predominantly developed within Western frameworks and may not adequately capture culturally embedded expressions of empathy in Indonesia. This study aims to develop and validate the Indonesian Cultural Empathy Scale (ICES) by constructing contextually grounded indicators and examining its factorial structure and construct validity. An exploratory sequential mixed-methods design was employed, beginning with qualitative inquiry through interviews, observation, and documentation to identify core domains of cultural empathy. These domains were integrated with ethnocultural empathy theory and the 18 National Character Pillars to construct scale indicators and items, which were subsequently evaluated through expert judgment. The quantitative phase involved large-scale survey administration and factor-based validation analysis. The findings reveal a stable two-factor structure reflecting intercultural openness and interfaith tolerance. Overall, ICES demonstrates conceptual coherence and cultural relevance, offering a value-based model of empathy measurement that contributes to the advancement of culturally responsive psychometric development in multicultural contexts.